2010
DOI: 10.1093/ndt/gfq477
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in tropical acute febrile illness in a tertiary care centre--RIFLE criteria validation

Abstract: The incidence of AKI in the common tropical acute febrile illnesses in our study such as scrub typhus, falciparum malaria, enteric fever, dengue and leptospirosis is 41.1%. RIFLE classification is valid and applicable in AKI related to tropical acute febrile illnesses, with an incremental risk of mortality and dialysis requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 34 publications
7
97
2
Order By: Relevance
“…In this study, 35.8% of the patients developed AKI, which is consistent with findings in other studies where its incidence has been reported ranging from 10 to 60%. [32][33][34][35][36] Most of the patients had stage 1 and 2 AKI comprising of 66% and 33% respectively and only 1% of patients had stage 3 AKI.…”
Section: -33mentioning
confidence: 99%
“…In this study, 35.8% of the patients developed AKI, which is consistent with findings in other studies where its incidence has been reported ranging from 10 to 60%. [32][33][34][35][36] Most of the patients had stage 1 and 2 AKI comprising of 66% and 33% respectively and only 1% of patients had stage 3 AKI.…”
Section: -33mentioning
confidence: 99%
“…In a study on 367 consecutively enrolled adult inpatients of a tertiary hospital in southern India, with tropical acute febrile illness due to scrub typhus, malaria, enteric fever, dengue, leptospirosis and undifferentiated acute febrile illness, the incidence of AKI was 41.1 % [1]. Scrub typhus accounted for the majority (51.2 %) of tropical acute febrile illnesses in this study.…”
mentioning
confidence: 64%
“…To the Editor: Tropical acute febrile illnesses have been described as important causes of acute kidney injury (AKI) in developing countries [1][2][3][4]. There is renewal of interest with emergence of such diseases in the developed countries and non-tropical regions as well, due to global warming and travel to tropics [5].…”
mentioning
confidence: 99%
“…Most studies report an incidence of AKI of 10-40%, which is very similar to that of our results. 15,16,19,31,32 However, the slightly lower incidence of AKI noted in other studies is likely because of inclusion of patients outside the intensive care unit. In a small prospective observational study 32 of 100 critically ill patients from North India, Paudel et al reported 33% incidence of AKI based on AKIN criteria and very high mortality rate in patients with AKI (93.3%) as well as non-AKI patients (53.7%).…”
Section: Discussionmentioning
confidence: 86%
“…Very few studies have attempted to explore the epidemiology of AKI in India. [15][16][17][18][19][20] However, these studies have either evaluated specific patient population or included patients outside the ICU, pediatric patients or have not used RIFLE or AKIN criteria to define, stratify or prognosticate AKI. Hence, in this study we aim to explore the epidemiology of AKI using both the RIFLE and AKIN criteria and to determine the prognostic validity of these criteria in an Indian ICU.…”
Section: Introductionmentioning
confidence: 99%